Resistance of Widows in Deepa Mehta’s Water - Sharma, Bimala (Literary Studies, 2020)
Deepa Mehta’s Water (2005), set in 1938 explores the lives of widows in an ashram in Varanasi, India, narrates the story of bodies that enter into the machinery of power.